Manajemen Life Skill untuk Membentuk Kemandirian pada Anak Berkebutuhan Khusus di SLB Negeri Tamanwinangun Kebumen - Agus Salim Chamidi; Aisyah Utami (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Insitut Agama Islam Nahdlatul Ulama (IAINU) Kebumen, 2020)
This research-based article is motivated by the importance of knowing the efforts to manage life skill education for children with special needs (ABK). The research aims to identify, describe, and analyze the planning, organizing, implementation, and evaluation in the management of life skill education for children with special needs (ABK). The research location is at the State Special School (SLB Negeri) Tamanwinangun Kebumen. In particular, the research paper is focused on the SMALB Class for the deaf in sewing practice. The research is qualitative. Data collection was taken by the method of observation, in-depth interviews and documentation. Analysis of the validity of the data is done by triangulation technique. The result of the research is that the educational process is oriented towards the development of personal, social, academic, and vocational skills. Management of life skill education at SLB Negeri Tamanwinangun is carried out through a process of planning, implementation, evaluation, and at the same time improvement whose cycles coincide. Recommendations, sewing practice activities need more time, and more practice facilities are needed, and the involvement of parents of students needs to be maximized.